INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN BERAU: INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN BERAU - Abdul Hakim (ECO-BUILD, 2019)
The Regulation of the Minister of Administrative Reforms No. 14 in 2017 as a regards of Drafting Guidelines of Public Satisfaction Surveys, Public Service Provider Units certify that the State Civil Service (ASN) should providing services to the community professionally. Professionalism highly determined by a person’s competence and capability in working. Related to the services, it could not be establish optimally without the readiness of the State Civil Apparatus to enforce their tasks and responsibilities in serving the community. Based on the results of this study, the conclusions can be drawn as follow : The measurement results of the Community Satisfaction Index at Investment and One Stop Integrated Services Board of Berau Regency totally was 79.01 with B / "Good" service unit category. Relatively, the services in Investment and One Stop Integrated Services Board of Berau Regency categorized as good service by means of the service requirements fulfilled easily, service procedures not convoluted,licensing services also on time, service fees appropriated with the service standards, service results was in accordance with people’s expectation , the staff’s competence was adequate /proficient in serving section, The staff provided an excellent service, and resolved complaints that have been equipped with facilities. From those 9 service indicators indicated that the indicators categorized in a good category, in other word it interpreted by B value